Brentuximab vedotin plus nivolumab after autologous haematopoietic stem-cell transplantation for adult patients with high-risk classic Hodgkin lymphoma: a multicentre, phase 2 trial. Issue 1 (January 2023) - Herrera, Alex F; Chen, Lu; Nieto, Yago; Holmberg, Leona; Johnston, Patrick; Mei, Matthew; Popplewell, Leslie; Armenian, Saro; Cao, Thai; Farol, Leonardo; Sahebi, Firoozeh; Spielberger, Ricardo; et al.
Summary: Background: After autologous haematopoietic stem-cell transplantation (HSCT), consolidation with brentuximab vedotin in patients with high-risk relapsed or refractory classic Hodgkin lymphoma has been shown to improve progression-free survival compared with placebo. Brentuximab vedotin plus nivolumab is a safe and effective treatment for relapsed or refractory classic Hodgkin lymphoma; therefore, we aimed to evaluate the safety and activity of this drug combination post-autologous HSCT consolidation in patients with high-risk relapsed or refractory classic Hodgkin lymphoma. Methods: We did a multicentre phase 2 trial at five centres in the USA. Eligible patients were aged 18 years or older with high-risk relapsed or refractory classic Hodgkin lymphoma, had an ECOG performance status of 0–2, and had adequate organ and bone marrow function. Enrolled patients received brentuximab vedotin (1·8 mg/kg) and nivolumab (3 mg/kg) intravenously starting 30–60 days after autologous HSCT on day 1 of each 21-day cycle for up to 8 cycles. Nivolumab dose reduction was not allowed. Brentuximab vedotin dose reduction to 1·2 mg/kg was permitted. If one drug was discontinued because of a toxic effect, the other could be continued. The primary endpoint was 18-month progression-free survival in all treated patients. This study is registered with ClinicalTrials.gov, number NCT03057795 . Findings: Between May 3, 2017, and July 13, 2019, 59 patients were enrolled and received the study therapy. Patients initiated brentuximab vedotin plus nivolumab for a median of 54 days (IQR 46–58) after autologous HSCT and received a median of 8 cycles (8–8). 34 (58%) of 59 patients were male, 29 (49%) completed 8 cycles of brentuximab vedotin plus nivolumab, and 45 (76%) completed 8 cycles of at least one drug. The median follow-up time was 29·9 months (IQR 24·6–34·8). The 18-month progression-free survival in all 59 patients was 94% (95% CI 84–98). The most common adverse events were sensory peripheral neuropathy (31 [53%] of 59) and neutropenia (25 [42%]), and immune-related adverse events requiring corticosteroids occurred in 17 (29%) of 59 patients. No treatment-related deaths were observed. Interpretation: Brentuximab vedotin plus nivolumab was highly active post-autologous HSCT consolidation for patients with high-risk relapsed or refractory classic Hodgkin lymphoma, most of whom had previous exposure to either brentuximab vedotin or PD-1 blockade. Combination immunotherapy in this setting should be further studied in patients with classic Hodgkin lymphoma with further refinement of the regimen to mitigate toxic effects, particularly in high-risk patients in whom more intensive therapy to prevent relapse is warranted. Funding: Bristol Myers Squibb, Leukemia and Lymphoma Society, Lymphoma Research Foundation, and National Cancer Institute of the National Institutes of Health.